Interventions in asthma and COPD - Mandovra, Neha P.; Leuppi, Jörg D.; Herth, Felix; Chhajed, Prashant N. (Therapeutische Umschau, 2019)
Advanced emphysema and asthma constitute major health burden worldwide and are associated with significant morbidity and mortality. Pharmacological options are limited. Researches are being carried out aiming to modify the natural course of both the diseases. Lung volume reduction surgeries are performed in advanced emphysema but are associated with significant morbidity and prolonged hospital stay. Various minimally invasive bronchoscopic methods have been developed with the goal of achieving clinical benefits of volume reduction surgery but lower complications. Bronchial thermoplasty is a bronchoscopic method of delivering controlled heat in the airways to reduce airway smooth muscle mass, thereby reducing bronchoconstriction in patients with severe asthma who remain uncontrolled despite optimal medical therapy. Various randomised controlled trials have been performed to evaluate the safety and efficacy of various endoscopic treatments like valves, coils, use of sclerosants and targeted lung denervation for severe emphysema and bronchial thermoplasty in severe asthma. The current review summaries the clinical trial evidence available for lung volume reduction in emphysema and thermoplasty in asthma and provide guidance for optimal patient selection for various therapies available.